The Influence of Commitment and Job Satisfaction on Employee Performance in Megamendung Bogor - Abubakar Iskandar; Agus Suarman Sudarsa; Salman Faruq Fadhlullah (Newinera Publisher, 2024)
The aim of this research is to determine the effect of commitment and job satisfaction on employee performance in the Bogor Megamendung detective training. This research uses a quantitative method, namely a research method that is post-positivism, namely researching a certain population or sample, where data collection uses research instruments and statistical data analysis with the aim of testing the hypotheses that have been determined so that direct or indirect relationships between variables can be identified. The number of respondents taken was 55 people. Several data collection methods were used, namely questionnaires, direct observation, literature study, documentation. Technical data analysis uses a Likert scale and regression method through the SPSS program. The research results show data that commitment has a positive effect on employee performance, job satisfaction has a positive effect on employee performance, commitment and job satisfaction have a positive effect on employee performance.